2007
DOI: 10.1007/s11064-006-9254-0
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial OXPHOS Functions in R1H Rhabdomyosarcoma and Skeletal Muscles of the Rat

Abstract: The aim of the study was to determinate mitochondrial oxidative phosphorylation (OXPHOS) functions in rat rhabdomyosarcoma R1H (R1H) and rat skeletal muscles. For that purpose skinned fiber technique and multiple substrate inhibitor titration were adapted to tumor samples. In our animal tumor model (R1H) functional abnormalities of OXPHOS were found compared to skeletal muscles. In R1H the state 3 respiration of pyruvate + malate was decreased: 0.56 +/- 0.28 nmol O(2)/mg/min versus 2.32 +/- 1.19 nmol O(2)/mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Importantly, of the mitochondrial respiratory chain complexes, complex I was the most severely impaired [34]. Together with the observation that complex I activity is reduced in R1H cells [35], our report that cardiolipin content is strongly decreased in R1H cells may thus contribute to explain the decrease in the respiratory capacity of R1H cells. Overall, these data suggest that a tight regulation between protein and phospholipid syntheses is necessary to produce functional mitochondria.…”
Section: Discussionsupporting
confidence: 66%
“…Importantly, of the mitochondrial respiratory chain complexes, complex I was the most severely impaired [34]. Together with the observation that complex I activity is reduced in R1H cells [35], our report that cardiolipin content is strongly decreased in R1H cells may thus contribute to explain the decrease in the respiratory capacity of R1H cells. Overall, these data suggest that a tight regulation between protein and phospholipid syntheses is necessary to produce functional mitochondria.…”
Section: Discussionsupporting
confidence: 66%
“…Other reasons for that might be related to specific impairments of mitochondria. In cancer cells, the mitochondria are characterized by defective respiratory chain complexes I and III and decreased β-F 1 -ATPase [ 279 291 ], and the type of mitochondrial impairment appears to determine the clinical phenotype [ 279 , 290 ]. Accordingly, benign oncocytomas are characterized by impaired complex I, but enhanced expression of other respiratory chain complexes and matrix enzymes, together with upregulation of mitochondrial tissue content, the latter changes likely compensating the insufficient complex I.…”
Section: Involvement Of Mitochondria In Pathological Processes and DImentioning
confidence: 99%
“…More specific, functional abnormalities of the respiratory chain complexes were found, in contrast to muscle cells. In R1H a decrease of complex I-activity and a varied ratio of pyruvate-dependent succinate respiration in favor of succinate respiration were verified 57 .…”
Section: Bioenergetic Properties and Metabolic Vulnerabilitiesmentioning
confidence: 87%
“…This deficiency in mitochondrial respiration probably contributes to the inability of R1H cells to decrease mitochondrial H 2 O 2 level at the onset of differentiation 56 . Further, it is showed that in R1H not only the amount of mitochondria was decreased, but also those tumor mitochondria present specific functional properties 57 . More specific, functional abnormalities of the respiratory chain complexes were found, in contrast to muscle cells.…”
Section: Bioenergetic Properties and Metabolic Vulnerabilitiesmentioning
confidence: 97%